Outcomes of fertility preservation in women with endometriosis: comparison of progestin-primed ovarian stimulation versus antagonist protocols - Emmanuelle Mathieu d'Argent; Clément Ferrier; Chrysoula Zacharopoulou; Naouel Ahdad-Yata; Anne-Sophie Boudy; Adèle Cantalloube; Rachel Levy; Jean-Marie Antoine; Emile Daraï; Sofiane Bendifallah (BMC, 2020)
Abstract Background PPOS protocols, initially described for FP in women with cancer, have many advantages compared to antagonist protocols. PPOS protocols were not evaluated for women with endometriosis. The objective of the study was to describe fertility preservation outcomes in women with endometriosis and to compare an antagonist protocol with a Progestin-Primed Ovarian Stimulation (PPOS) protocol. Method We conducted a prospective cohort study associated with a cost-effectiveness analysis in a tertiary-care university hospital. The measured outcomes included the numbers of retrieved and vitrified oocytes, and direct medical costs. In the whole population, unique and multiple linear regressions analysis were performed to search for a correlation between individual characteristics and the number of retrieved oocyte. Results We included 108 women with endometriosis who had a single stimulation cycle performed with either an antagonist or a PPOS protocol. Overall, 8.1 ± 6.6 oocytes were retrieved and 6.4 ± 5.6 oocytes vitrified per patient. In the multiple regression model, age (p = 0.001), prior ovarian surgery (p = 0.035), and anti-Mullerian hormone level (p = 0.001) were associated with the number of retrieved oocytes. Fifty-four women were stimulated with an antagonist protocol, and 54 with a PPOS protocol. A mean of 7.9 ± 7.4 oocytes were retrieved in the antagonist group and 8.2 ± 5.6 in the PPOS group (p = 0.78). A mean of 6.4 ± 6.4 oocytes were vitrified in the antagonist group and 6.4 ± 4.7 in the PPOS group (p = 1). In the cost-effectiveness analysis, the PPOS protocol was strongly dominant over the antagonist protocol. Conclusion Fertility preservation procedures are feasible and effective for patients affected by endometriosis. Antagonist and PPOS protocols were associated with similar results but the medico-economic analysis was in favor of PPOS protocols.